1968
DOI: 10.1128/jb.96.3.860-861.1968
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analyses of the cell wall of the murine leprosy bacillus

Abstract: The taxonomy of murine leprosy bacillus, as a species of genus Mycobacterium, is not yet established. Based on morphological characteristics during limited growth in vitro, Uyeda (4) argued that this microorganism should not be classified as a mycobacterium, but rather should be in a new genus related to Nocardia. However, the chemical composition of the cell wall (arabinose, galactose, and mucopeptide) is qualitatively similar to that of other mycobacteria (1). Since a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The chemical composition of cell walls of various mycobacteria (M. phlei, M. rhodochrous, M. tuberculosis, M. bovis, M. smegmatis, M. lepraemurium, Mycobacterium sp., and murine leprosy bacillus) has been studied qualitatively (2,34,76) and quantitatively (78,180,181,255). The cell walls always contained the amino acids Ala, Glu, m-Dpm and the monosaccharides arabinose and galactose.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…The chemical composition of cell walls of various mycobacteria (M. phlei, M. rhodochrous, M. tuberculosis, M. bovis, M. smegmatis, M. lepraemurium, Mycobacterium sp., and murine leprosy bacillus) has been studied qualitatively (2,34,76) and quantitatively (78,180,181,255). The cell walls always contained the amino acids Ala, Glu, m-Dpm and the monosaccharides arabinose and galactose.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…These infected tissues were prepared in the National Hansen's Disease Center and supplied through the National Institutes of Health. d M. lepraemurium was isolated from spleens and mesenteric nodules of infected Swiss white mice as previously described (16). ' ATCC, American Type Culture Collection.…”
mentioning
confidence: 99%
“…Uyeda (18,19) claimed that, from the morphological features of this bacillus, it should not be classified as a mycobacterium, but rather should be placed in a new genus related to nocardia. However, results of recent works on the chemical analysis of the M. lepraemurium cell wall (7)(8)(9)14) suggest that its chemical composition qualitatively resembles that of the cell walls of mycobacteria (15). Also, Fukui and co-workers (12) have reported that the crude extracts of eight strains of M. lepraemurium contain a cross-reactive material whose antigenic determinants are partially in common with an alpha antigen of Mycobacterium avium.…”
mentioning
confidence: 99%